Breast Implant–Associated Anaplastic Large-Cell Lymphoma in Brazil: What Are We Missing?. Issue 5 (22nd August 2022) - Groth, Anne K.; Clemens, Mark W.; Graf, Ruth; Sebastião, Ana P.; Azambuja, Ana P.; Louveira, Maria H.; Urban, Linei A. B. D.; Batista, Bernardo N.
Abstract : Background: Breast implant–associated anaplastic large-cell lymphoma (BIA-ALCL) has been diagnosed in more than 1000 patients in more than 30 countries, although only a few cases have been reported in Latin America and the Caribbean to date. As the second-largest global market for breast implants with a predominance of textured-surface implants, Brazil is a major global market for cosmetic augmentations, making it unlikely that cases of BIA-ALCL are actually scarce. Methods: A local and voluntary registry of patients with BIA-ALCL was initiated in 2018. All patients diagnosed with BIA-ALCL were confirmed by the World Health Organization criteria. Implant characteristics, disease symptoms, treatment, and oncologic outcomes were assessed. Results: Fourteen cases of BIA-ALCL in a Brazilian population were identified in the Paraná state. Disease-specific diagnostic tests were omitted before surgical intervention in 50 percent of patients. With additional cases from a literature review, the treatment and outcomes of 29 cases of BIA-ALCL in Brazil were assessed. Conclusions: Compared with other populations, these initial observations suggest that awareness of the disease by the local breast surgery community remains low and that a number of cases may remain undiagnosed. Lack of preoperative diagnostic testing compromises disease treatment, oncologic outcomes, and both short- and long-term surveillance.